4‐Aminoquinolines Bearing a 1, 3‐Benzodioxole Moiety: Synthesis and Biological Evaluation as Potential Antifungal Agents. Issue 5 (15th April 2021) - Yang, Rui; Li, Zhuolin; Xie, Jialing; Liu, Jianchuan; Qin, Tianhong; Liu, Junda; Du, Haiying; Ye, Haoyun
Abstract: In search of new environmentally friendly and effective antifungal agents, a series of 4‐aminoquinolines bearing a 1, 3‐benzodioxole moiety were prepared and their structures were fully elucidated by spectroscopic analyses. The antifungal activities of all the target compounds against five phytopathogenic fungi were evaluated in vitro . The results revealed that most of the newly synthesized compounds exhibited obvious inhibitory activities at the concentration of 50 μg/mL. Among them, 6‐(furan‐2‐yl)‐ N ‐(4‐methylphenyl)‐2 H ‐[1, 3]dioxolo[4, 5‐ g ]quinolin‐8‐amine hydrochloride (7m ) displayed more promising antifungal potency with EC50 values of 10.3 and 14.0 μg/mL against C. lunata and A. alternate, respectively. Particularly, the EC50 value of 7m against C. lunata was 7.3‐fold as potent as the standard azoxystrobin. There were some significant morphological alterations in the mycelia of C. lunata when treated with 7m at 50 μg/mL. Additionally, the preliminary structure–activity relationships (SARs) were also discussed. Thus, this study suggests that 4‐aminoquinolines bearing a 1, 3‐benzodioxole moiety are interesting scaffolds for the development of novel antifungal agents. Abstract :